2021
DOI: 10.1080/22797254.2021.1960201
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of trophic state in lakes and reservoirs of Wuhan using Sentinel-2 satellite data

Abstract: With the rapid development of economy, many lakes in Wuhan have been polluted to different degrees and suffer from eutrophication. The main objective of this study was to conduct the monthly trophic state assessments of waters in Wuhan from March 2019 to June 2020 using 111 Sentinel-2 images. The Forel-Ule index (FUI) and empirical Gaussian process regression (GPR) were, respectively, applied to obtain monthly area percentage (AP) of waters with each trophic state. Both FUI-derived and empirical GPR-retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…We can use the two‐dimensional CIE x – y chromaticity diagram to digitally specify the color as three RGB values (i.e., reflectance) using the following equations (Fairman et al., 1997): centerX=2.7689normalR+1.7517normalG+1.1302normalBY=1.0000normalR+4.5907normalG+0.0601normalBZ=0.0000normalR+0.0565normalG+5.5934normalB \begin{align*}X=2.7689\mathrm{R}+1.7517\mathrm{G}+1.1302\mathrm{B}\\ Y=1.0000\mathrm{R}+4.5907\mathrm{G}+0.0601\mathrm{B}\\ Z=0.0000\mathrm{R}+0.0565\mathrm{G}+5.5934\mathrm{B}\end{align*} x=X/(X+Y+Z) $x=X/(X+Y+Z)$ y=Y/(X+Y+Z) $y=Y/(X+Y+Z)$ where R, G, and B represent the reflectance at the red, green, and blue wavelengths, respectively. Water color reflects the first‐order description of water quality (Zhou et al., 2021), and the majority of reported algal blooms in inland freshwater lakes are greenish in color in China (Hou et al., 2022). We acknowledge that blooms with other colors, either cyanobacteria or other bloom species, were excluded from our CIE‐based method; such blooms were also identified in many regions, especially in brackish lakes (Dierssen et al., 2006; Lopez et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can use the two‐dimensional CIE x – y chromaticity diagram to digitally specify the color as three RGB values (i.e., reflectance) using the following equations (Fairman et al., 1997): centerX=2.7689normalR+1.7517normalG+1.1302normalBY=1.0000normalR+4.5907normalG+0.0601normalBZ=0.0000normalR+0.0565normalG+5.5934normalB \begin{align*}X=2.7689\mathrm{R}+1.7517\mathrm{G}+1.1302\mathrm{B}\\ Y=1.0000\mathrm{R}+4.5907\mathrm{G}+0.0601\mathrm{B}\\ Z=0.0000\mathrm{R}+0.0565\mathrm{G}+5.5934\mathrm{B}\end{align*} x=X/(X+Y+Z) $x=X/(X+Y+Z)$ y=Y/(X+Y+Z) $y=Y/(X+Y+Z)$ where R, G, and B represent the reflectance at the red, green, and blue wavelengths, respectively. Water color reflects the first‐order description of water quality (Zhou et al., 2021), and the majority of reported algal blooms in inland freshwater lakes are greenish in color in China (Hou et al., 2022). We acknowledge that blooms with other colors, either cyanobacteria or other bloom species, were excluded from our CIE‐based method; such blooms were also identified in many regions, especially in brackish lakes (Dierssen et al., 2006; Lopez et al., 2008).…”
Section: Methodsmentioning
confidence: 99%
“…where R, G, and B represent the reflectance at the red, green, and blue wavelengths, respectively. Water color reflects the first-order description of water quality (Zhou et al, 2021), and the majority of reported algal blooms in inland freshwater lakes are greenish in color in China (Hou et al, 2022). We acknowledge that blooms with other colors, either cyanobacteria or other bloom species, were excluded from our CIE-based method; such blooms were also identified in many regions, especially in brackish lakes (Dierssen et al, 2006;Lopez et al, 2008).…”
Section: Algal Bloom Detection Algorithmmentioning
confidence: 99%
“…This observation suggests a recurrent temporal variability of water colour, which may depend on seasonal cycles. In addition to climatic variables, certain boundary conditions, such as land cover and hydrology of the lake basin or the proximity of anthropogenic activities, are additional factors that influence water colour [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Since their launch in 2015 and 2017, respectively, these sensors have provided 10-to-60 m resolution, depending on the spectral band, with a combined 5-day revisit frequency. Previous studies indicate S2 may be well suited for deriving chl a in lakes and reservoirs, for example in Europe [35][36][37], South America [38][39][40], Asia [41][42][43][44], the U.S. [45,46], and across a global set of lakes, with a rigorous validation across North America [47,48]. However, these studies tend to focus on individual or a limited number of lakes.…”
Section: Introductionmentioning
confidence: 99%